2010
DOI: 10.1016/j.ajog.2010.03.045
|View full text |Cite
|
Sign up to set email alerts
|

Timing of elective repeat cesarean delivery at term and neonatal outcomes: a cost analysis

Abstract: Objective The purpose of this investigation was to examine the economic impact of performing elective repeat cesarean during the 37th or 38th week of gestation relative to the ACOG recommendation of 39 week delivery. Methods Decision analysis modeling was used to estimate economic outcomes for a hypothetical cohort of neonates using data from the NICHD/MFMU study entitled “Timing of elective repeat cesarean delivery at term and neonatal outcomes.” Costs and charges were estimated using the Florida Healthcare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 13 publications
2
32
1
1
Order By: Relevance
“…The reasons for this are as follows (8)(9)(10)(11)(12)(13)(14). 1-There is less activity of amiloride-sensitive sodium channels in alveolar epithelial cells following cesarean section, leading to reduced fluid clearance.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for this are as follows (8)(9)(10)(11)(12)(13)(14). 1-There is less activity of amiloride-sensitive sodium channels in alveolar epithelial cells following cesarean section, leading to reduced fluid clearance.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, the rate increased from 20.7% in 1996 to 31.8% in 2007, while in the Netherlands, it increased from 8.5% in 1993 to 15.1% in 2007 (Hamilton et al 2006;Robinson et al 2010;Wilmink et al 2010;Kamiya 2013). The increase at general hospitals in Japan has also been quite marked, rising from 9.9% in 1987 to 24.1% in 2011.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that there is 2% increased chance of NICU admission for baby who delivered at 38 weeks. 13,25 According to Okeke et al 22.6%, babies needed NICU admission ≤38 weeks, whereas at 39 weeks only 1.8% babies needed NICU admission. 23 But according to Wilmink et al there is only 1% increase in chance of NICU admission at 38-38+6 weeks who undergo elective LSCS.…”
Section: Discussionmentioning
confidence: 99%